Assessing The Quality of Educational Services in Nyala University From The Perspectives of Students - Statistical Study - Abdelgalal Othman Idris (University of Science and Technology, Yemen, 2016)
Abstract The problem of the study is represented in students' views, as recipients, towards the educational services, and what are the factors of educational services in university of Nyala. The study aims at assessing the quality of educational services identifying the services' main factorsfrom students' points of views. The study population are the students themselves. A stratified random sample has been designed and data-based questionnaire is collected. The sample size was 476 units. A descriptive statistics, factor analysis and chi square test were used as statistical tools. For extraction factors the principal components were used whereas varimax for rotation and Kaiser criterion were used for the number of factors. Data is analyzed using software package of SPSS. After the literature review, results were discussed and the researcher has come up to the following findings: There are seven factors covering the Educational Services; including: academic staff, employees, reputation, facilities, transportation, restrooms and umbrellas and the means of communication devices. Factors above explain 60.08 % of the total variance.  Male and female students views are differently expressed on educational services quality, where no significant difference on quality of services in term of different academic levels. As for students no differences have been recorded in both scientific and theoretical studies.